Short communication longitudinal variation in the concentrations of C, N and P in the stem of Echinochloa polystachya (H.B.K.) Hitchcock - Pompêo, Marcelo Lutz Martins [UNESP]; Henry, Raoul [UNESP] (My University, 1997)
The Concentrations of C, N and P were determined in the internodes of the stem of Echinochloa polystachya (H.B.K.) Hitchcock with the aim of showing their longitudinal distributions. The concentrations ranged from 421.93 to 466.03 mgCgDW-1; from 2.78 to 13.61 mg N gDW-1 and from 0.151 to 1.074 mg P gDW-1. N and P concentrations increased towards the apical direction of the stem. C concentrations showed an inverse trend. These distributions suggest that N and P are transported to the apical region of the stem, while the majority of the C compounds observed in the distal region must be retained in the supporting structure of the plant.
Keywords: Aquatic macrophyte; Chemical composition; Echinochloa polystachya